Geoscience of Climate and Energy 6. Tree Rings as Temperature Proxies - Luckman, Brian (Geoscience Canada, 2010)
SUMMARY Tree rings have provided annually resolved and precisely dated proxy climate records for large areas of the earth’s land surface. These records are considerably longer than instrumental climate data and allow the reconstruction of climate history, trends and patterns over a wide range of temporal and spatial scales. This paper briefly reviews the principles and assumptions that underlie the reconstruction of temperatures from tree-ring data, and provides three examples of their application at differing spatial and temporal scales over the last millennium.